The electronics of radio - Rutledge, David B. (Cambridge University Press, 1999)
This innovative book provides a stimulating introduction to analog electronics by analyzing the design and construction of a radio transceiver. The author provides essential theoretical background at each step, along with carefully designed laboratory and homework exercises. This structured approach ensures a good grasp of basic electronics as well as an excellent foundation in wireless communications systems.